2022
DOI: 10.3390/agriculture12081207
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Neural Network-Based Method for Detecting Estrus Behavior in Ewes

Abstract: We propose a lightweight neural network-based method to detect the estrus behavior of ewes. Our suggested method is mainly proposed to solve the problem of not being able to detect ewe estrus behavior in a timely and accurate manner in large-scale meat sheep farms. The three main steps of our proposed methodology include constructing the dataset, improving the network structure, and detecting the ewe estrus behavior based on the lightweight network. First, the dataset was constructed by capturing images from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…MobileNetV2 had the highest FPS of 54.39, which improved by 46.29% compared to CSPDarknet53. Although the model size of EfficientNetV2 was found to be significantly lower than that of CSPDarknet53, FPS decreased rather than increased, unlike the results published in other studies [42,43], which may be caused by the compatibility of the experimental hardware platform with the model inference process. The training loss value of different models all plummeted at the 70th epoch, which may be caused by the change of learning rate during model training.…”
Section: Lightweight Convolutional Neural Networkcontrasting
confidence: 70%
“…MobileNetV2 had the highest FPS of 54.39, which improved by 46.29% compared to CSPDarknet53. Although the model size of EfficientNetV2 was found to be significantly lower than that of CSPDarknet53, FPS decreased rather than increased, unlike the results published in other studies [42,43], which may be caused by the compatibility of the experimental hardware platform with the model inference process. The training loss value of different models all plummeted at the 70th epoch, which may be caused by the change of learning rate during model training.…”
Section: Lightweight Convolutional Neural Networkcontrasting
confidence: 70%
“…Automated estrus detection using sensors, infrared thermography and machine learning models is not limited to sows only. Considerable progress is evident in cow [141][142][143][144], buffalo [23,145], and ewe [146,147] estrus detection as well. Though installing and implementing real-time estrus detection systems may require an initial investment, in the long run, will result in benefits and significant cost savings for livestock farmers and industries.…”
Section: Benefits Of Technology and Ai-based Estrus Detectionmentioning
confidence: 99%
“…The experimental results showed that the accuracy of this model for pig gesture recognition was above 93% with FPS between 10 and 12, which still has the disadvantage of slow recognition speed. 2022 Yu L et al proposed using E cientNet, a lightweight neural network, as a feature extraction network for YOLOv3 and added a SENet attention mechanism to detect the oestrus behavior of female sheep, achieving 99.44% accuracy 7 . In addition, there are some object detection studies on sh and ducks that suggest the feasibility of applying deep learning to animals [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%